Ultrasound analysis of hemidiaphragm function in case of pleural effusion - Martin Boussuges; Martin Boussuges; Fabienne Bregeon; Fabienne Bregeon; Xavier Benoit D’Journo; Alain Boussuges; Alain Boussuges (Frontiers in Medicine)
BackgroundDiaphragm dysfunction is frequently observed in patients with pleural effusion. The aim of the study was to determine the criteria for estimating the impact of pleural fluid on diaphragm function and detecting impairment of diaphragmatic muscle.MethodsThis was a retrospective observational study carried out in a university hospital. Cases of free pleural effusion were recruited from the ultrasound consultation of the lung function test laboratory. The quantification of pleural effusion and analysis of diaphragmatic function were performed using chest ultrasound performed while sitting. In case of abnormal diaphragmatic motion, the examination was repeated in supine position.Results109 pleural effusions (57 left, 52 right) were included in the analysis. Pleural effusions were detected after thoracic surgery in 89% of cases and in the context of medical disease in other cases. Excursion during deep inspiration was reduced by the amount of fluid (4.3 ± 2.1 cm for small effusions, 3.2 ± 1.7 cm for moderate effusions and 1.1 ± 1.8 cm for large effusions). In 23 cases of large pleural effusion, the excursions during deep inspiration were always below the lower limit of normal. In some cases, a paradoxical motion suggesting hemidiaphragm paralysis was observed. When the inspiratory thickening was normal, the paradoxical excursions disappeared in supine position. In moderate pleural effusion (53 cases), hemidiaphragm excursion was above lower limit of normal in 68% of cases. In cases of paradoxical motions, repeated ultrasound examinations were in favor of hemidiaphragm paralysis. In small pleural effusion (32 cases) the excursion was most often normal.ConclusionThe ultrasound analysis of diaphragm excursion and thickening in sitting and supine positions is useful to assess the impact of pleural effusion and detect impairment in diaphragm muscle function.